INSULIN-MIMETIC ACTIVITY OF STEVIOSIDE ON DIABETIC RATS: BIOCHEMICAL, MOLECULAR AND HISTOPATHOLOGICAL STUDY - Saleh, Osama M.; Awad, Nabil S.; Soliman, Mohamed M.; Mansour, Ahmed A.; Nassan, Mohammed A. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Stevioside has been used as a medication for reducing glucose levels in diabetic patients. The exact mode of action is still unclear. Therefore, the current study outlines the molecular and biological roles of stevioside in treatment of diabetes. Materials and Methods: induced diabetic male wistar rats treated with stivioside and metformin as therapy for diabetic rats. Biochemical, molecular and histopathological studies have been done to evaluate the therapeutic effect of stevioside on minimizing levels of glucose in diabetic rats.Results: Stevioside administration normalized kidney and liver biomarkers, restored alterations in antioxidants activity and lipid profiles. Moreover, stevioside increased insulin and leptin secretion that are decreased in diabetic rats to the normal levels.For mRNA expression, stevioside up-regulated the expressions of PK and IRS-1 genes which are down-regulated in diabetic rats, and was very effective in down-regulation of CPT-1 mRNA expression. At the cellular levels; stevioside normalized the histopathological changes induced in pancreas. Conclusion: Stevioside has insulin like effects and it is useful for diabetic patient’s therapy.